2003
DOI: 10.1002/syn.10232
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine displaces [3H]domperidone from high‐affinity sites of the dopamine D2 receptor, but not [3H]raclopride or [3H]spiperone in isotonic medium: Implications for human positron emission tomography

Abstract: Because the high-affinity state of the dopamine D2 receptor, D2High, is the functional state of the receptor, has a role in demarcating typical from atypical antipsychotics, and is markedly elevated in amphetamine-sensitized rats, it is important to have a method for the convenient detection of this state by a ligand. The present data show that, in contrast to [(3)H]spiperone or [(3)H]raclopride, [(3)H]domperidone labels D2High sites in the presence of isotonic NaCl in either striatum or cloned D2Long receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 36 publications
4
96
0
Order By: Relevance
“…13,17,20 In addition, because receptor agonists accelerate the exchange of receptor-bound GDP for GTP, the stimulation of [ 35 S]GTP-g-S incorporation is a useful index of agonist action. Phencyclidine and ketamine also increased the incorporation of [ 35 S]GTP-g-S into cloned D2-containing cells 8 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,17,20 In addition, because receptor agonists accelerate the exchange of receptor-bound GDP for GTP, the stimulation of [ 35 S]GTP-g-S incorporation is a useful index of agonist action. Phencyclidine and ketamine also increased the incorporation of [ 35 S]GTP-g-S into cloned D2-containing cells 8 (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 Although early experiments did not reveal the D1-D2 link in any rat striatum or in every human striatum, 11 recent work, using a competition method, has consistently revealed the D1-D2 link in rat and human striata. 10 This recent work showed that the block of D1 receptors unveiled the presence of a highaffinity state for D2 in a dopamine/[ 3 H]raclopride competition-type experiment, with a dopamine dissociation constant of 1.5 nM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the Kd of [ 3 H]domperidone is 0.47 nM at D2 receptors in rat striatum, the final concentration of 2 nM occupied 81% of the D2 receptors, using the equation f = C/(C + Kd), where f is the fraction of receptors occupied by [ 3 H]domperidone, and C is 2 nM (Seeman, et al, 2003).…”
Section: Tissue Collectionmentioning
confidence: 99%